Effectiveness of Acceptance and Commitment Therapy on Distress Tolerance and Life Meaning in Depressed Women - Amani Firouzabad, Khadijeh; Sayari Merkieh, Maryam; Daemi Juybari, Sharifeh; Hamidi Menesh, Kiana; Rouhafza , Mahboubeh (Psychology of Woman Journal, 2023)
Objective: The present study aimed to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on distress tolerance and life meaning in depressed women. Methods and Materials: The research method was a quasi-experimental pre-test-post-test with a control group. The population consisted of depressed women seeking help at counseling clinics in Tehran in the year 2022. From this population, 30 individuals were selected through convenience sampling and randomly assigned into two groups: an experimental group (15 individuals) and a control group (15 individuals); the instruments used for data collection were the Distress Tolerance and Life Meaning questionnaires. The ACT protocol was administered to the experimental group over 8 sessions, twice a week, each lasting 120 minutes, while no intervention was applied to the control group. Findings: The findings indicated that the average scores of distress tolerance and life meaning in the post-test were significantly improved compared to the pre-test in the experimental group. Conclusion: Therefore, Acceptance and Commitment Therapy has an impact on distress tolerance and life meaning in depressed women.